Cognitive behavioral treatment of insomnia : a session-by-session guide - Perlis, Michael L. (Springer, 2008)
Cognitive behavior therapy which has been adapted to treat so many problems, has also brought data-driven and data-yielding treatment to insomnia.Focusing on this evidence-based modality, Cognitive Behavioral Treatment of Insomnia is a much-needed treatment manual that provides clinicians with the why's and how's of this approach in concise and practical terms